Postmortem serotonin level in cerebrospinal fluid as a marker of the manner of death - Damjanjuk, Irina; Popović, Vesna; Lukić, Vera; Soldatović, Ivan; Mihailović, Zoran; Atanasijević, Tatjana (Vojnosanitetski pregled, 2021)
Background/Aim. Serotonin [5-hydroxytriptanine (5-HT)], as a neurotransmitter in the central nervous system, is included in the regulation of autonomic and cognitive functions, sensory processing, motor activity, emotions, mood, and almost every kind of behavior. In forensic investigations of death, 5-HT has been studied in different body fluids, regarding the cause of death, particularly in suicides and drug abuse or as a marker of an acute stress response. The aim of this study was to establish 5-HT levels in cerebrospinal fluid (CSF) as a marker of its central activity during fatal event in deaths different in manner, particularly in cases where the victims were aware of the stressful event. Methods. Study sample consisted of 81 postmortem CSF obtained during autopsy. Concentrations of the 5-HT were established regarding natural versus violent (accidents, homicides and suicides) deaths. After preparation, samples were analyzed through the liquid chromatography-tandem mass spectrometry method. Results. Violent deaths had significantly higher 5-HT levels (U = 519.000; p < 0.05). Differences were found in mean values among different causes of death (higher in blunt injury, stabbing and intoxication, while lower in cardiac deaths and hypothermia) but without statistical significance. 5-HT levels significantly differed among age groups (χ2 = 13.354; p = 0.001), with the tendency to decrease with age. No differences in 5-HT levels were observed regarding gender, length of agony period, and awareness of impending lethal outcome. The values tended to increase with postmortem interval albeit without significant differences. Conclusion. Serotonin could be a useful postmortem biochemical marker to distinguish natural and violent death, regardless of individual variability in concentrations.